BUDAYA KOMUNIKASI WARGA MADURA - Fajrie, Mahfudlah (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractTh e diversity of the existing cultures in an area emerged the di? erences of communication cultures as well. Th e communication cultures of Maduraâs people with especially Javanese in Jepara are certainly di? erent. Th e formulations of the problem in this study are (1) how are the communication cultures in aspect of language use conducted by Maduraâs people who worked as the barber in Tahunan Jepara regency? (2) How are the symbols in the communication process conducted by Maduraâs people in Tahunan Jepara regency?. Th is research used ? eld research method and ethnograpy approach. Th e data in this research were gained through observation, interview, and documentation. Th e data analysis used cultural theme analysis. Th e data validity in this research used the triangulation technique of data (source). Th e results of this research are: (1) the communication cultures of Maduraâs people who worked as the barbers in Tahunan Jepara are loudly and clearly intonation in communication. In addition, they directly express the intention and purpose of their speaking. Languages used by the barbers from Madura with the customers are Javanese and Indonesia language. However, they use Madura language to communicate with their fellows. (2) Th e symbols used by the Maduraâs barbers in communicating are verbal symbol called oral communication and non-verbal symbol called body language. Th e symbol of body language is the shaking of the head as the sign that they do not understand what the customers mean. Th e other way, the body language by pitching of the head is as the sign of agreement and understanding of communication purpose.Keyword: Culture, Communication, Madura.